Laser welding of fusion relevant steels for the European DEMO - Kirk, Simon; Suder, Wojciech; Keogh, Keelan; Tremethick, Tristan; Loving, Anthony B. (Elsevier, 2018)
The construction and maintenance of the European DEMO will require reliable joining of thick-walled Eurofer97 steel cooling pipes between in-vessel components in the reactor. To this end, laser welding has been investigated as a potential method for pipe joining. Two different techniques (keyhole laser welding and hybrid laser-laser welding) were used to produce test welds in Eurofer97 and P91 steel samples. Welds were also produced using different filler wires to reduce the hardness in the weldment region and improve the weld profile. Optical microscopy and hardness mapping were used to assess the quality of the welds produced. From the weld trials, suitable process parameters were identified that resulted in fully penetrated welds with good profiles. Here, we will present the results of the laser welding development process and the properties of the welds produced using these two techniques.
Keywords: DEMO; Laser welding; Mechanical properties; Service pipes